Green photonics: photonic integrated circuits for optical communications and sensing based on organic-inorganic hybrids - Bastos, Ana Rita Naia (2019)
The present work aims the production and characterization of cost-effective photonic integrated circuits (PICs) to encounter green photonics goals, namely in the optical communications and sensing fields. Therefore, organic-inorganic hybrids (di-ureasil and tri-ureasil), doped with zirconium propoxide stabilized with methacrylic acid, were synthesized by the versatile sol-gel methodology, at room temperature, as planar waveguides processed in the form of monoliths, with controlled shape and size, and films with variable thickness (10−5-10−6 m) in vitreous or silicon oxide substrates. They exhibit stable and tunable properties, mechanical and thermal stability resulting from the synergy between the organic and inorganic counterparts. Their main feature is the heavily facilitated control of the surface optical properties by the inherent flexibility offered by these materials that are easily self-patterned by direct UV laser writing, and the refractive index tuning through chemical doping. The influence of different concentrations of zirconia-based clusters (20-60 mol%) in the local structure of di-ureasils and tri-ureasils was studied through X-ray diffraction, nuclear magnetic resonance of 13C and 29Si atoms, infrared spectroscopy by Fourier transform, Raman spectroscopy by Fourier transform and thermogravimetry analysis. The relevant optical features for applications in PICs were determined, showing acceptable attenuation values (∼1-5 dB·cm−1) for low dimension circuits, and reduced insertion losses arising from the fibre-device similar refractive index (1.49-1.52). Taking advantage of the material photosensibility, direct UV laser writing was used to pattern the desired optical architecture on the surface of organic-inorganic hybrids. In what concerns optical communications, passive and active devices were produced: a thermo-optic integrated variable wave plate device to control the state of polarization of an optical signal, showing a linear retardation coefficient of 17±1 °/°C; a 90° hybrid coupler to demodulate a 20 Gb/s quadrature phase shift keying transmission over 40 km of fibre, yielding a 2.5 dB power penalty, relatively to back-to-back; an electro-optic phase modulator based on a Mach-Zehnder interferometer (MZI) with a voltage shift required for a π phase change of 2.9±0.3 V; an optical amplifier in the blue spectral region for visible light communications with a maximum optical gain efficiency of 1.62±0.02 cm∙μJ−1. In the sensing field, the development of portable low-cost PICs based biosensors for lab-on-a-chip devices are of great interest. Thus, a biosensor based on an MZI was produced to monitor the growing concentration of bacteria in a liquid medium, presenting a sensitivity of 2×10−4 RIU and limit of detection of 2.0 pg·mm−3.